The Effect of Using Collaborative Learning Activities to Reduce Speaking Anxiety - Nabila, Esa; Artha, Dewi Juni; Tussa'diah, Halimah (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
This study aims to examine the effects of using collaborative learning activities in reducing students' speaking anxiety. Collaborative learning methods are expected to have a positive impact on students' speaking skills by increasing their active participation in class. This study used an emotional intelligence scale and a Likert scale-based questionnaire to reveal aspects of collaborative learning. The results of this study are 1) normality text is Kolmogorov-Smirnov sig value on Tests of Normality For control class is VIII-1 with pretest significance0.154 0.005 and post test 0.036 0.005 while For class experiment that is class VIII-2 with pretest VIII-2 significance 0.200 0.005 and post test 0.124 0.005; 2) Homogenity text second variable value the sign is 0.700 and 0.81 shows that the data is homogeneous because mark significance 0.005. This matter show that in study This No there is similarity variance from moderate variable tested; 3) Hypotesis Testing obtained The t value is 23.158 and the sig value . (2 tailed) is 0.000 0.005. The results of the study are expected to be applied in schools to improve the quality of education and provide valuable experience for researchers in conducting action research related to collaborative learning.